Banhasasim-Tang Treatment Reduces the Severity of Esophageal Mucosal Ulcer on Chronic Acid Reflux Esophagitis in Rats. (2nd March 2017) - Shin, Mi-Rae; Seo, Bu-Il; Son, Chang Gue; Roh, Seong-Soo; An, Hyo-Jin
Abstract : The present study was conducted to evaluate both antioxidant and anti-inflammatory activity of Banhasasim-tang (BHSST) on chronic acid reflux esophagitis (CRE) model. Rat CRE model was established operatively and then treated with BHSST (1 g/kg body weight per day) for 15 days Esophageal pathological changes were analyzed using macroscopic examination and hematoxylin/eosin staining. The antioxidant and inflammatory protein levels were determined using Western blotting. The administration of BHSST significantly reduced both the overexpression of serum reactive oxygen species (ROS) and an excessive formation of thiobarbituric acid-reactive substances (TBARS) in esophagus tissue. Thus, the severity of esophageal ulcer was lower in BHSST treated rats than control rats on the gross and histological evaluation. Nuclear factor-erythroid 2-related factor 2 (Nrf2) led to the upregulation of antioxidant enzyme including SOD, GPx-1/2, and HO-1 by binding to antioxidant response element (ARE). Moreover, BHSST administration markedly reduced the expression of inflammatory proteins through mitogen-activated protein kinase- (MAPK-) related signaling pathways and decreased significantly the protein expressions of inflammatory mediators and cytokines by inhibition of nuclear factor-kappa B (NF- κ B) activation. Taken together, these results support the fact that BHSST administration can suppress the development of esophageal mucosal ulcer via regulating inflammation through the activation of the antioxidant pathway.